The methodology of ibn al-Nadim in the study of Hinduism with special reference to his kitab al-Fihrist - Shehu, Fatmir Mehdi (2019)
This study seeks to examine the methodology of Ibn al-Nadim, the classical Muslim scholar, in the study of Hinduism with special reference to his master piece al-Fihrist. The aim of this research is to investigate Ibn Nadim’s documentary method consisting of descriptive and analytical approaches. He classified the narrated or reported historical data about Hinduism and its main teachings based on the information presented to him by different sources during his time. This research is very significant as it suggests new insights for young scholars of comparative religion in dealing with Hinduism as addressed by the content of Ibn al-Nadim’s original writing. This study focuses its discussion on: (1) Ibn Nadim’s brief chronology, (2) the content of his selected work on the study of religion – al-Fihrist, and (3) his methodology in the study of Hinduism through selected statements from the original script. Descriptive and analytical methods are used in this research. The expected findings of this scientific paper will add to contemporary scholarship of comparative religion the insights of the original work of a classical Muslim scholar in the study of Hinduism.